2011
DOI: 10.1007/s12665-011-1187-5
|View full text |Cite
|
Sign up to set email alerts
|

Spatial simulation of evapotranspiration of semi-arid Inner Mongolian grassland based on MODIS and eddy covariance data

Abstract: In semi-arid regions of Central Asia, water shortage results from low annual precipitation (P) with high interannual variability. Evapotranspiration (ET) dominates water balance losses entirely. Previous studies showed large differences between individual grassland sites in the partitioning of ET into evaporation and transpiration, but only little difference in the evaporative ratio ET/P. The hydrological model BROOK90 was applied to the Xilin river catchment in Inner Mongolia (China) in combination with data … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
20
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 22 publications
(21 citation statements)
references
References 31 publications
1
20
0
Order By: Relevance
“…Despite the above uncertainties, this study confirmed the spatiotemporal variations in ET 0 and also indicated the dominant factors in the two time series as reported in many previous studies Liu et al 2011b;Zhang et al 2013). Furthermore, we also recommend that more attention should be paid to actual evapotranspiration (ET a ) (Vetter et al 2012), especially in response to climate change and human activities. For example, we can acquire the spatiotemporal ET a for a particular region or basin with ET a products (Cai et al 2014;Li et al 2014b;Xue et al 2013), or construct better ET a model for our own study area with more precise forcing datasets (Minderlein and Menzel 2015;Yin et al 2013;Zhang et al 2008b).…”
Section: Climate Factors Trendsupporting
confidence: 88%
“…Despite the above uncertainties, this study confirmed the spatiotemporal variations in ET 0 and also indicated the dominant factors in the two time series as reported in many previous studies Liu et al 2011b;Zhang et al 2013). Furthermore, we also recommend that more attention should be paid to actual evapotranspiration (ET a ) (Vetter et al 2012), especially in response to climate change and human activities. For example, we can acquire the spatiotemporal ET a for a particular region or basin with ET a products (Cai et al 2014;Li et al 2014b;Xue et al 2013), or construct better ET a model for our own study area with more precise forcing datasets (Minderlein and Menzel 2015;Yin et al 2013;Zhang et al 2008b).…”
Section: Climate Factors Trendsupporting
confidence: 88%
“…Fan et al, 2007) and process-based land surface models (e.g. Vetter et al, 2012). These procedures often demand far-reaching assumptions, such as the closure of the energy and water balances (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…One of the focus region is Central Asia (Mongolia and Inner Mongolia), where project partners are focussing among others on environmental simulation (Vetter et al 2011), socio-economical aspects (Sigel et al 2011) and IWRM implementation (Horlemann and Dombrowsky 2011).…”
Section: Introductionmentioning
confidence: 99%